2016
DOI: 10.1111/nph.14301
|View full text |Cite
|
Sign up to set email alerts
|

Respiration climacteric in tomato fruits elucidated by constraint‐based modelling

Abstract: Summary Tomato is a model organism to study the development of fleshy fruit including ripening initiation. Unfortunately, few studies deal with the brief phase of accelerated ripening associated with the respiration climacteric because of practical problems involved in measuring fruit respiration.Because constraint‐based modelling allows predicting accurate metabolic fluxes, we investigated the respiration and energy dissipation of fruit pericarp at the breaker stage using a detailed stoichiometric model of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 46 publications
5
40
0
1
Order By: Relevance
“…Since fruit of slightly different ages harbour different profiles of primary compounds, we could assume that central metabolism is tuned to fruit growth, more specifically soluble sugars, amino and organic acids. This agrees with previous phenotyping and modelling studies on tomato that demonstrate metabolic shifts in carbon metabolism in the growing fruit [25,28,29,31]. Furthermore, it has been recently confirmed through transcriptomics and proteomics that the developing fruit not only undergoes metabolic shifts in central pathways, but also redox metabolism, such as for pyridine nucleotides that are detrimental to energy homeostasis [27,32,33].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since fruit of slightly different ages harbour different profiles of primary compounds, we could assume that central metabolism is tuned to fruit growth, more specifically soluble sugars, amino and organic acids. This agrees with previous phenotyping and modelling studies on tomato that demonstrate metabolic shifts in carbon metabolism in the growing fruit [25,28,29,31]. Furthermore, it has been recently confirmed through transcriptomics and proteomics that the developing fruit not only undergoes metabolic shifts in central pathways, but also redox metabolism, such as for pyridine nucleotides that are detrimental to energy homeostasis [27,32,33].…”
Section: Discussionsupporting
confidence: 90%
“…PCA explained 83% of the maximal variance in the dataset and resulted in a separation of fruit by developmental characteristics (i.e., the first and second fruit versus the third fruit) rather than by pathosystems ( Figure 3B). Hence, this multivariate differentiation indicates that the profiles of primary metabolites mostly respond to the developmental stage of the fruit, which supports the idea that central metabolism is tuned to fruit growth [27][28][29]. Complementarily, two-factor ANOVA (P < 0.05) only generated significant markers for the inoculation factor (4; 36%), including sucrose, fructose, glutamate and fumarate (Table 1 and Figure S1).…”
Section: Global Metabolomics After Baba Treatment and After Inoculationsupporting
confidence: 75%
“…Finally, the GrOE-FBA model predicts metabolic fluxes by flux optimization and does not account for signalling and regulation of metabolism, although these could be included in the form of experimental constraints on maximal enzyme activity. As a result, the model we present does not activate flux through energy dissipation mechanisms (such as alternative NADH dehydrogenases and alternative oxidase) and hence the GrOE-FBA model is unable to predict the respiratory climacteric (Colombié et al, 2017). A computationally expensive FBA approach called costweighted flux minimization has been shown to be capable of predicting alternative pathways in source leaves (Cheung et al, 2015).…”
Section: Groe-fba: Limitations Of the Approachmentioning
confidence: 89%
“…but cannot answer the question "Why is it happening?". For example, with this approach it has been shown that breakdown of transitory starch is the underlying cause of the respiratory climacteric in tomato fruit (Colombié et al, 2017) but it was not possible to explain the purpose of the transitory starch accumulation. This is because starch accumulation and degradation were constraints of the model and not predictions.…”
Section: Groe-fba: Application To Tomato Fruit Developmentmentioning
confidence: 99%
“…Dessa forma, as alterações físicas, químicas, bioquímicas e fisiológicas no amadurecimento dos tomates são controladas pela respiração e pelos níveis de etileno(FAGUNDES et al, 2015), que podem ser influenciados de maneira significativa de acordo com o microclima dentro dos sacos. SegundoColombié et al (2017) fluxos metabólicos como a respiração no estágio de maturação estão envolvidos com a degradação do amido e das paredes celulares, o que pode melhorar a qualidade do tomate através de uma maior relação entre açúcares e ácidos(BERTIN et al, 2018).Quanto à produtividade, no experimento de primavera-verão a alta incidência de problemas fisiológicos e alta incidência de pinta preta do tomateiro (Alternaria solani) e outros patógenos, inviabilizaram a condução até o final do ciclo de cultivo, não permitindo a obtenção de análises de produtividade e rentabilidade Fialho et al (2009). que verificaram que a média da produtividade de tomates ensacados se manteve próxima da média dos não ensacados.A expressão genética dos híbridos pode variar conforme o material utilizado nas embalagens, devido a alterações em processos metabólicos, como a supressão da expressão gênica relacionada à síntese de lignina, que melhora significativamente a qualidade e aspectos da aparência(MISHRA et al, 2017;WANG et al, 2017;.Em relação aos teores de sólidos solúveis (brix), não houve diferença entre as embalagens no híbrido Carina Star.…”
unclassified